KEPATUHAN NOTARIS DALAM MELAKSANAKAN KETENTUAN KETENAGAKERJAAN TERHADAP KARYAWANNYA (Studi Kantor Notaris Di Pekanbaru) - Elsharia Tampubolon; Budiman Ginting; Henry Sinaga (Jurnal Hukum dan Bisnis (Selisik), 2021)
Notary is a profession that has good prestige and dignity in the eyes of society.Notaries are considered good because they run their offices to help the communityin making authentic deeds, and also as public officials, who should understand,know, and understand the law. Both the law theoretically and the law in practice.However, it is undeniable that the profession that is pinned on a Notary, there aresome individuals who do not carry out or apply the law properly, even though he isa dignified and dignified profession. must be subject to and comply with the law,but must also comply with other laws and regulations. In Pekanbaru City, that thereare still Notaries who provide salaries below the UMK that has been set by thelocal government. This reflects the notary's non-compliance with other laws andregulations other than the notary position law